1, 3-Dioxane inside fullerenes: the innovative conformational behavior of usual cyclic system. Issue 3 (4th March 2021) - Kuramshina, Albina E.; Bochkor, Svetlana A.; Kuznetsov, Valerij V.
Abstract: Conformational transformations of unsubstituted 1, 3-dioxane in the cavities of fullerenes with 60, 70 and 80 atoms in their shells have been investigated using PBE/3ζ density functional theory method. It was shown that the preferred conformation of the guest molecule in endoclasters with 60 atoms (С60, С12 B24 N24, B36 N24 ) corresponds to the 1, 4-twist form, not to the expected chair . In case of fullerenes C70 and C80 conformational equilibrium is shifted to the chair, but the relative stability of 1, 4-twist -form is higher in comparison with free 1.3-dioxane. Substitution carbon atoms of the last nanostructures by boron-nitrogen fragments again resulted in the dominance of 1, 4-twist conformer. In all cases the molecule of 1, 3-dioxane inside fullerenes has a notable electric charge and demonstrates a significant reduction in bond lengths.